An Empirical Study of the Effect of Power Law Distribution on the Interpretation of OO Metrics. (30th January 2013) - Shatnawi, Raed; Althebyan, Qutaibah
Abstract : Context . Software metrics are surrogates of software quality. Software metrics can be used to find possible problems or chances for improvements in software quality. However, software metrics are numbers that are not easy to interpret. Previous analysis of software metrics has shown fat tails in the distribution. The skewness and fat tails of such data are properties of many statistical distributions and more importantly the phenomena of the power law. These statistical properties affect the interpretation of software quality metrics. Objectives . The objective of this research is to validate the effect of power laws on the interpretation of software metrics. Method . To investigate the effect of power law properties on software quality, we study five open-source systems to investigate the distribution and their effect on fault prediction models. Results . Study shows that power law behavior has an effect on the interpretation and usage of software metrics and in particular the CK metrics. Many metrics have shown a power law behavior. Threshold values are derived from the properties of the power law distribution when applied to open-source systems. Conclusion . The properties of a power law distribution can be effective in improving the fault-proneness models by setting reasonable threshold values.